Case Study as an Active Method of Teaching Business English; Procedia - Social and Behavioral Sciences; Vol. 166 : Proceedings of The International Conference on Research Paradigms Transformation in Social Sciences 2014 (RPTSS-2014), 16–18 October 2014, Tomsk, Russia - Bekisheva T. G. Tatiana Gennadievna (2015, 2015)
Title screen